Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Balancing the modulation of soy protein structure to achieve improved texture and reduced antigenicity in soy yogurt: A practical approach of proteolytic pretreatment and lactic acid bacteria fermentation - Qiyuan Lu; Xinran Guo; Xia Fan; Benjamin K. Simpson; Wei Li; Xin Rui (Food Chemistry, 2026)

Fire–Moisture Interactions Shape Recovery Trajectories Across Temperate Vegetation Communities - Emily K. Simpson; Glenda M. Wardle; Christopher R. Dickman; Aaron C. Greenville (Global Change Biology, 2026)
The recovery of vegetation following fire is increasingly shaped by concurrent climate‐driven hydrological extremes, such as drought and extreme precipitation. Under these multi‐disturbance scenarios vegetation communities are likely to show different recovery thresholds and trajectories of change, but this is yet to be fully understood or quantified. We used the Greater Blue Mountains World Heritage Area in south‐eastern Australia as a model system to assess how sustained moisture surplus or deficit could differentially influence the recovery of forest, heath and wetland vegetation from low‐extreme severity fire. From 2015 to 2024, this region experienced severe drought, extensive bushfires (the ‘Black Summer’ bushfires) and extreme rainfall events. By using a new remote‐sensing index (the Post‐fire Stability Index) that measures the rate of change in a disturbed system, we found that most vegetation communities could recover following low‐severity fire even in the case of poor soil moisture conditions, but moisture became increasingly limiting as burn severity increased. Certain communities, such as wet sclerophyll forests and freshwater wetlands, experienced disproportionate declines (up to times greater than other communities) as burn severity and drought intensified. These communities are likely at greatest risk as climate drying escalates. We stress that future recovery from fire in temperate communities will be governed not only by the characteristics of the fire itself and those of the affected vegetation community, but also by the extent to which these characteristics interact with prevailing hydro‐climatic conditions.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Early Devonian (Lochkovian–Pragian) linguliform brachiopods from the Cobar Supergroup, western New South Wales, Australia - James L. Valentine; David K. Mathieson; Andrew J. Simpson (Palaeoworld, 2026)

Metals exposures and telomere length as a marker of DNA damage among electronic waste workers and a reference group - Mabel Sarpong Duah; Ibrahim Issah; Shirley V. Simpson; Serwaa A. Bawua; Duah Dwomoh; Joseph K. H. Bonney; Shinsaku Inomata; Thomas G. Robins; Niladri Basu; Arima Hiroaki; Julius N. Fobil (Environmental Science and Pollution Research, 2026)

Pea-wheat composite bread: Effects of milling methods and NIR spectral insights - Mariana Maçãs; Barbara Biduski; Alessandro Ferragina; Antonia A.L. dos Santos; Jeremy C. Simpson; Margaritha M. Mysior; Mahesha M. Poojary; Elke K. Arendt; Eimear Gallagher (Innovative Food Science & Emerging Technologies, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

We are what ‘we’ eat: How do close social relationship dynamics in the household impact the sustainability of diets? - Tess Davis; Sophie Duncan; Rebecca Gregson; Emma Garnett; Jared Piazza; Sharon Simpson; Esther K. Papies (Appetite, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Implications of improved remote sensing capabilities on blue carbon quantification - Steven W.J. Canty; Miguel Cifuentes-Jara; Jorge Herrera-Silveira; Hannah K. Morrissette; Jordan R. Cissell; Joanna Acosta-Velázquez; Emil Cherrington; Ilka C. Feller; Daniel A. Friess; Jonathan S. Lefcheck; Loraé T. Simpson; Claudia Teutli-Hernandez (Estuarine, Coastal and Shelf Science, 2025)

Scope effects and willingness to pay for deep sea management practices within and beyond national jurisdictions - Bui Bich Xuan; Claire W. Armstrong; Stephen Hynes; Isaac Ankamah-Yeboah; Katherine Simpson; Godwin K. Vondolia (Journal of Environmental Management, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Challenges to Seagrass Restoration in the Indian River Lagoon, Florida - Vivienne A. Main; Morgan K. Gilligan; Sarah M. Cole; Todd Z. Osborne; Ashley R. Smyth; Loraé T. Simpson (Journal of Marine Science and Engineering, 2024)
Seagrasses provide valuable ecosystem services, including improved water quality, carbon sequestration, and sediment stabilization. Unfortunately, these critical habitats are declining globally due to a range of anthropogenic impacts. Restoration practitioners have made efforts to mitigate loss through the introduction of seagrass transplants. However, seagrass restoration has low success rates and is plagued by water quality concerns and ecosystem degradation. Studies to improve seagrass restoration efforts have targeted different functional taxa to allow for greater stability and recovery of threatened ecosystems, and excluded macro-grazers to limit losses to newly established and restored seagrasses. We hypothesized greater seagrass (Halodule wrightii) health when restored in conjunction with hard clams (Mercenaria mercenaria) and protected from grazers using herbivore exclusion devices (HEDs) in the Indian River Lagoon (IRL), Florida. While our study experienced high rates of seagrass mortality, we were able to observe significant differences in seagrass health between IRL sub-lagoons and observed the positive effects of HEDs on seagrass health. The observed high species mortality highlights how restoration in the IRL is hindered by biotic and abiotic stressors, site selection, and a lack of clear restoration protocols. As we see ongoing declines in water quality and loss of foundational species, informed site selection, greater understanding of grazer presence, and multi-species restoration will provide an informed approach for future seagrass restoration projects globally.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Human biomonitoring of dioxins, furans, and non-ortho dioxin-like polychlorinated biphenyls (PCBs) in blood plasma from Old Crow, Yukon, Canada (2019) - Ashlyn K. Simpson; Mallory Drysdale; Mary Gamberg; Ken Froese; Jeremy Brammer; Pierre Dumas; Mylène Ratelle; Kelly Skinner; Brian D. Laird (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Construction of hypoallergenic microgel by soy major allergen β-conglycinin through enzymatic hydrolysis and lactic acid bacteria fermentation - Yumeng Fu; Xinran Guo; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2024)

The last of US: survival of cryopreserved salamander sperm depends on cryodiluent - Devin Chen; Li-Dunn Chen; Shaina S. Lampert; Austin Simpson; Carrie K. Kouba; Andy J. Kouba (Cryobiology, 2023)

Modulation of soy protein immunoreactivity by different matrix structures of lactic acid bacterium-induced soy protein gels: Epitope destruction during in vitro gastroduodenal digestion and absorption - Yaqiong Wang; Yumeng Fu; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2023)

Do global change variables alter mangrove decomposition? A systematic review - Loraé T. Simpson; Samantha K. Chapman; Lance M. Simpson; Julia A. Cherry (Global Ecology and Biogeography, 2023)
Aim Global change is expected to modify the magnitude and trajectory of organic matter decomposition in mangrove ecosystems. Yet, the degree and direction of that change is unknown, especially considering the large C storage potential that mangroves provide. We performed a systematic review of primary literature to examine the relationships between genus‐specific litter quality, latitude or other global change proxies and decomposition of mangrove litter fractions. Location Global. Time Period 1976–2021. Taxon Mangroves. Methods We compiled a dataset of 480 decomposition rates, including species, litter fraction, latitude, and relevant biophysical data. We investigated the influence of genera, tissue type, latitude, and global change proxies on decomposition rates using linear models and qualitative approaches. We also performed calculations to determine the potential importance of the decomposition process on the root litter biomass C pool in the context of blue C significance. Results Collectively, latitudinal relationships suggest that factors other than temperature, such as tissue type and genus, may regulate decay rates within mangroves' distributional range. Decay rates of leaf litter, roots, and wood converged on a value of 0.009 ± 0.0005, 0.002 ± 0.0001, and 0.001 ± 0.0003, respectively, across continents and geomorphological settings. Our calculations suggest that small changes in decomposition rate will not elicit large changes in blue C storage potential. Conclusions The main drivers behind variability in mangrove biomass decay rates detected across the distributional range remain uncertain. However, the small latitudinal range that mangroves inhabit and the submerged environment within which litter decomposes suggest that decay depends on species‐specific responses or biotic interactions among species to global change drivers. Few studies have examined global change impacts directly, and variability in decay and lack of representation of some mangrove groups in the literature suggest that implications for blue C are important to consider.

Blue carbon pathways for climate mitigation: Known, emerging and unlikely - Jennifer Howard; Ariana E. Sutton-Grier; Lindsey S. Smart; Christian C. Lopes; Jill Hamilton; Joan Kleypas; Stefanie Simpson; Jennifer McGowan; Albert Pessarrodona; Heidi K. Alleway; Emily Landis (Marine Policy, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Improving the representation of groundwater processes in a large-scale water resources model - Helen Elizabeth Baron; Virginie D. J. Keller; R. Horan; Donald John MacAllister; Mike Simpson; Christopher R. Jackson; Helen A. Houghton-Carr; Nathan Rickards; Kaushal K. Garg; Muddu Sekhar; Alan MacDonald; Gwyn Rees (Hydrological Sciences Journal, 2023)

Nitrogen Addition Increases Freeze Resistance in Black Mangrove (Avicennia germinans) Shrubs in a Temperate-Tropical Ecotone - Ilka C. Feller; Uta Berger; Samantha K. Chapman; Emily M. Dangremond; Nicole G. Dix; J. Adam Langley; Catherine E. Lovelock; Todd Z. Osborne; Audrey C. Shor; Loraé T. Simpson (Ecosystems, 2023)

Trade-off between microbial carbon use efficiency and specific nutrient-acquiring extracellular enzyme activities under reduced oxygen - Ji Chen; Irene Cordero; Daryl L. Moorhead; Jennifer K. Rowntree; Loraé T. Simpson; Richard D. Bardgett; Hayley Craig (Soil Ecology Letters, 2023)

Usability of existing global and national data for flood related vulnerability assessment in Indonesia - Breanne K. Langlois; Elizabeth Marsh; Tyler Stotland; Ryan B. Simpson; Katherine Berry; David A. Carroll; Aris Ismanto; Magaly Koch; Elena N. Naumova (Science of The Total Environment, 2023)

Pectin from plantain peels: Green recovery for transformation into reinforced packaging films - Jiayu Xie; Yi Zhang; Sappasith Klomklao; Benjamin K. Simpson (Waste Management, 2023)

Contrasting Effects of Nitrogen Addition on Leaf Photosynthesis and Respiration in Black Mangrove in North Florida - Matthew A. Sturchio; Jeff Chieppa; Lorae T. Simpson; Ilka C. Feller; Samantha K. Chapman; Michael J. Aspinwall (Estuaries and Coasts, 2023)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

A method and its application to determine the amount of cannabinoids in sewage sludge and biosolids - Aaron J. Pandopulos; Bradley S. Simpson; Richard Bade; Jake W. O’Brien; Meena K. Yadav; Jason M. White; Cobus Gerber (Environmental Science and Pollution Research, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Light at night reduces digestive efficiency of developing birds: an experiment with king quail - Tuul Sepp; Emily Webb; Richard K. Simpson; Mathieu Giraudeau; Kevin J. McGraw; Pierce Hutton (The Science of Nature, 2021)

Food-related transglutaminase obtained from fish/shellfish - Yi Zhang; Benjamin K. Simpson (Critical Reviews in Food Science and Nutrition, 2020)

Quantifying Soft Tissue Artefacts and Imaging Variability in Motion Capture of the Fingers - C. D. Metcalf; C. Phillips; A. Forrester; J. Glodowski; K. Simpson; C. Everitt; A. Darekar; L. King; D. Warwick; A. S. Dickinson (Annals of Biomedical Engineering, 2020)
This study assessed the accuracy of marker-based kinematic analysis of the fingers, considering soft tissue artefacts (STA) and marker imaging uncertainty. We collected CT images of the hand from healthy volunteers with fingers in full extension, mid- and full-flexion, including motion capture markers. Bones and markers were segmented and meshed. The bone meshes for each volunteer’s scans were aligned using the proximal phalanx to study the proximal interphalangeal joint (PIP), and using the middle phalanx to study the distal interphalangeal joint (DIP). The angle changes between positions were extracted. The HAWK protocol was used to calculate PIP and DIP joint flexion angles in each position based on the marker centroids. Finally the marker locations were ‘corrected’ relative to the underlying bones, and the flexion angles recalculated. Static and dynamic marker imaging uncertainty was evaluated using a wand. A strong positive correlation was observed between marker- and CT-based joint angle changes with 0.980 and 0.892 regression slopes for PIP and DIP, respectively, and Root Mean Squared Errors below 4°. Notably for the PIP joint, correlation was worsened by STA correction. The 95% imaging uncertainty interval was

Envisioning a national invasive species information framework - Jamie K. Reaser; Annie Simpson; Gerald F. Guala; Jeffrey T. Morisette; Pam Fuller (Biological Invasions, 2020)
With a view toward creating a national Early Detection and Rapid Response Program (EDRR) program, the United States National Invasive Species Council Management Plan for 2016–2018 calls for a series of assessments of federal EDRR capacities, including the evaluation of “relevant federal information systems to provide the data and other information necessary for risk analyses/horizon scanning, rapid specimen identification, and rapid response planning.” This paper is a response to that directive. We provide an overview of information management needs for enacting EDRR and discuss challenges to meeting these needs. We then review the history of relevant US policy directives for advancing invasive species information systems and provide an overview of federal invasive species information system capacities, including current gaps and inconsistencies. We conclude with a summary of key principles and needs for establishing a national invasive species information framework. Our findings are consistent with earlier studies and, thus, emphasize the need to act on long-recognized needs. As a supplement to this paper, we have cataloged federal invasive species databases and information tools identified through this work.

Molecular Diagnosis of Emmonsia-Like Fungi Occurring in Wild Animals - P. Danesi; C. Falcaro; K. Dukik; Y. Jiang; A. P. Rizzoli; R. Allavena; V. Simpson; S. Ravagnan; C. Zanardello; G. Capelli; G. S. de Hoog (Mycopathologia, 2019)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

It's not just what you have, but how you use it: solar‐positional and behavioural effects on hummingbird colour appearance during courtship - Richard K. Simpson; Kevin J. McGraw (Ecology Letters, 2018)
Animals exhibit a diversity of colours that can play key roles in mating interactions. However, we presently lack an understanding of the relative importance of the environment, behaviour and natural reflective properties of colourful ornaments in shaping an individual's colour appearance during mating displays. We investigated interactions among structurally based plumage, display environments and courtship shuttle displays of male Costa's hummingbirds ( Calypte costae ) to test how these elements may differentially contribute to colour appearance during shuttles. Male position relative to the sun was the strongest predictor of colour appearance, with shuttle behaviours and feather reflectance playing smaller roles. Furthermore, male solar orientation and shuttling behaviour (e.g. shuttle width) were repeatable among displays, whereas male colour appearance mostly was not. These results emphasise the contributions of behaviour and environment to colour‐signalling and suggest that relying on reflectance measurements of colourful ornaments alone provides an incomplete picture of ecologically relevant visual phenotypes of displaying animals.

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Biological activity and LC-MS/MS profiling of extracts from the Australian medicinal plant Acacia ligulata (Fabaceae) - Diana Jæger; Bradley S. Simpson; Chi P. Ndi; Anna K. Jäger; Christoph Crocoll; Birger Lindberg Møller; Philip Weinstein; Susan J. Semple (Natural Product Research, 2018)

Differences in nutrient foraging among Trifolium subterraneum cultivars deliver improved P-acquisition efficiency - Rebecca E. Haling; Lawrie K. Brown; Adam Stefanski; Daniel R. Kidd; Megan H. Ryan; Graeme A. Sandral; Timothy S. George; Hans Lambers; Richard J. Simpson (Plant and Soil, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Phaseolus vulgaris lectins: A systematic review of characteristics and health implications - Shudong He; Benjamin K. Simpson; Hanju Sun; Michael O. Ngadi; Ying Ma; Tiemin Huang (Critical Reviews in Food Science and Nutrition, 2018)

Localised hydrodynamics influence vulnerability of coral communities to environmental disturbances - George Shedrawi; James L. Falter; Kim J. Friedman; Ryan J. Lowe; Morgan S. Pratchett; Christopher J. Simpson; Conrad W. Speed; Shaun K. Wilson; Zhenlin Zhang (Coral Reefs, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Acute oxytocin improves memory and gaze following in male but not female nursery-reared infant macaques - Elizabeth A. Simpson; Annika Paukner; Valentina Sclafani; Stefano S. K. Kaburu; Stephen J. Suomi; Pier F. Ferrari (Psychopharmacology, 2017)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Analysis of compound heterozygotes reveals that the mouse floxed Pax6 tm1Ued allele produces abnormal eye phenotypes - Natalie J. Dorà; Aaron J. F. Crookshanks; Karen K. Y. Leung; T. Ian Simpson; John O. Mason; David J. Price; John D. West (Transgenic Research, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Fitness level impacts salivary antimicrobial protein responses to a single bout of cycling exercise - Hawley Kunz; Nicolette C. Bishop; Guillaume Spielmann; Mira Pistillo; Justin Reed; Teja Ograjsek; Yoonjung Park; Satish K. Mehta; Duane L. Pierson; Richard J. Simpson (European Journal of Applied Physiology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Mapania multiflora, a distinctive new species of Cyperaceae (Mapanioideae) from Borneo - Z. Shabdin; A. Culham; D. A. Simpson; K. Meekiong (Kew Bulletin, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

The utility of optical remote sensing for characterizing changes in the photosynthetic efficiency of Norway maple saplings following transplantation - J.M. Atherton; C.J. Nichol; M. Mencuccini; K. Simpson (International Journal of Remote Sensing, 2013)

The Benefits of Spatially Targeted Water Level Management for Salinity Reduction in a Coastal Aquifer - I. P. Holman; K. R. Rushton; T. B. Simpson (Water Resources Management, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Volcanology and petrology of Mathews Tuya, northern British Columbia, Canada: glaciovolcanic constraints on interpretations of the 0.730 Ma Cordilleran paleoclimate - Benjamin R. Edwards; James K. Russell; Kirstie Simpson (Bulletin of Volcanology, 2011)

Occurrence and Concentration of Dissolved Silver in Rivers in England and Wales - A. Peters; P. Simpson; G. Merrington; K. Rothenbacher; L. Sturdy (Bulletin of Environmental Contamination and Toxicology, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Purification and properties of digestive lipases from Chinook salmon (Oncorhynchus tshawytscha) and New Zealand hoki (Macruronus novaezelandiae) - Ivan Kurtovic; Susan N. Marshall; Xin Zhao; Benjamin K. Simpson (Fish Physiology and Biochemistry, 2010)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Toxicity of Metals to the Bivalve Tellina deltoidalis and Relationships Between Metal Bioaccumulation and Metal Partitioning Between Seawater and Marine Sediments - C. K. King; M. C. Dowse; S. L. Simpson (Archives of Environmental Contamination and Toxicology, 2010)

A new subspecies of Coleochloa setifera (Cyperaceae) from Kenya - K. Hoenselaar; D. A. Simpson (Kew Bulletin, 2009)

Fuirena bidgoodae, a new species of Cyperaceae from East Africa - K. Hoenselaar; A. M. Muasya; D. A. Simpson (Kew Bulletin, 2009)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Sequence stratigraphy of Jurassic strata in the lower Surat Basin succession, Queensland - K. L. Hoffmann; J. M. Totterdell; O. Dixon; G. A. Simpson; A. T. Brakel; A. T. Wells; J. L. Mckellar (Australian Journal of Earth Sciences, 2009)

In Silico Construction of a Protein Interaction Landscape for Nucleotide Excision Repair - Nancy Tran; Ping-Ping Qu; Dennis A. Simpson; Laura Lindsey-Boltz; Xiaojun Guan; Charles P. Schmitt; Joseph G. Ibrahim; William K. Kaufmann (Cell Biochemistry and Biophysics, 2009)

Renal injury at first presentation as a predictor for poor outcome in severe paracetamol poisoning referred to a liver transplant unit - N. Pakravan; K. J. Simpson; W. S. Waring; C. M. Bates; D. N. Bateman (European Journal of Clinical Pharmacology, 2009)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

The development and mapping of functional markers in Fragaria and their transferability and potential for mapping in other genera - D. J. Sargent; A. Rys; S. Nier; D. W. Simpson; K. R. Tobutt (Theoretical and Applied Genetics, 2006)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

Uredinales species pathogenic on species of Myrtaceae - J. A. Simpson; K. Thomas; C. A. Grgurinovic (Australasian Plant Pathology, 2006)

A note on the relationship between temperature and water vapor over oceans, including sea surface temperature effects - C. -L. Shie; W. -K. Tao; J. Simpson (Advances in Atmospheric Sciences, 2006)

Geochemical Distribution and Bioavailability of Heavy Metals and Oxalate in Street Sediments from Rio de Janeiro, Brazil: A Preliminary Investigation - John J. McAlister; Bernard J. Smith; Jose Baptista Neto; Julia K. Simpson (Environmental Geochemistry and Health, 2005)

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria - D. J. Sargent; T. M. Davis; K. R. Tobutt; M. J. Wilkinson; N. H. Battey; D. W. Simpson (Theoretical and Applied Genetics, 2004)

An Assessment of Five Australian Polychaetes and Bivalves for Use in Whole-Sediment Toxicity Tests: Toxicity and Accumulation of Copper and Zinc from Water and Sediment - C. K. King; M. C. Dowse; S. L. Simpson; D. F. Jolley (Archives of Environmental Contamination and Toxicology, 2004)

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

Effect of exercise mode on blood glucose disposal during physiological hyperinsulinaemia in humans - K. Tsintzas; E. J. Simpson; N. Seevaratnam; S. Jones (European Journal of Applied Physiology, 2003)

Reproducibility of the blood lactate threshold, 4 mmol·l -1 marker, heart rate and ratings of perceived exertion during incremental treadmill exercise in humans - Grant S.; McMillan K.; Newell J.; Wood L.; Keatley S.; Simpson D.; Leslie K.; Fairlie-Clark S. (European Journal of Applied Physiology, 2002)

Murine model of BCG lung infection: Dynamics of lymphocyte subpopulations in lung interstitium and tracheal lymph nodes - Rajiv K. Saxena; David Weissman; Janet Simpson; Daniel M. Lewis (Journal of Biosciences, 2002)

Telescoped porphyry Cu-Mo-Au mineralisation, advanced argillic alteration and quartz-sulphide-gold-anhydrite veins in the Thames District, New Zealand - R. Brathwaite; M. Simpson; K. Faure; D. Skinner (Mineralium Deposita, 2001)

The Importance of Nitrogen Oxides for the Exceedance of Critical Thresholds in the Nordic Countries - M. Johansson; R. Suutari; J. Bak; G. Lövblad; M. Posch; D. Simpson; J.-P. Tuovinen; K. Tørseth (Water, Air, & Soil Pollution, 2001)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

A comparative transcript map and candidates for mutant phenotypes in the Tyrp1 (brown) deletion complex homologous to human 9p21-23 - Eleanor H. Simpson; Ruth Suffolk; Julia A. Bell; Siobhán A. Jordan; Dabney K. Johnson; Pat R. Hunsicker; Jack S. Weber; Monica J. Justice; Ian J. Jackson (Mammalian Genome, 2000)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Moxonidine and cognitive function: interactions with moclobemide and lorazepam - K. Wesnes; P. M. Simpson; B. Jansson; A. Grahnén; H.-J. Weimann; H. Küppers (European Journal of Clinical Pharmacology, 1997)

An expanded collection of mouse Y Chromosome RDA clones - David E. Bergstrom; Hailing Yan; Manjula M. Sonti; Sandya Narayanswami; Janet K. Bayleran; Elizabeth M. Simpson (Mammalian Genome, 1997)

An investigation of the temporal induction of cytokine mRNAs in LPS-challenged thioglycollate-elicited murine peritoneal macrophages using the reverse transcription polymerase chain reaction - A. E. C. M. Simpson; P. T. Tomkins; K. L. Cooper (Inflammation Research, 1997)

Serum protein polymorphism in common eiders detected by isoelectric focusing - Sheila M. Schmutz; Josef K. Schmutz; Nancy E. Simpson; Hinrich Tabel (Biochemical Genetics, 1987)

A comparative study of O'nyong nyong virus with Chikungunya virus and plaque variants - A. C. Chanas; Z. Hubalek; B. K. Johnson; D. I. H. Simpson (Archives of Virology, 1979)